State of the art report on video‐based graphics and video visualization - Borgo, Rita; Leitte, Heike (Computer graphics forum, 2012)
Abstract In recent years, a collection of new techniques which deal with video as input data, emerged in computer graphics and visualization. In this survey, we report the state of the art in video?based graphics and video visualization. We provide a review of techniques for making photo?realistic or artistic computer?generated imagery from videos, as well as methods for creating summary and/or abstract visual representations to reveal important features and events in videos. We provide a new taxonomy to categorize the concepts and techniques in this newly emerged body of knowledge. To support this review, we also give a concise overview of the major advances in automated video analysis, as some techniques in this field (e.g. feature extraction, detection, tracking and so on) have been featured in video?based modelling and rendering pipelines for graphics and visualization.